2020
DOI: 10.1039/c9nr08958f
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle formulated vaccines: opportunities and challenges

Abstract: The advancement in nanotechnology brings in unique opportunities to meet the challenges in immunology and vaccine development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 166 publications
0
59
0
2
Order By: Relevance
“…However, the genetic reversion of attenuated vaccines or infection of immunocompromised hosts, as well as the likely tumorgenicity of deactivated viruses, are essential safety issues. In addition, all microorganisms cannot be used as live vaccines, since some of them are extremely virulent and others are intrinsically immune evasive [175,176].…”
Section: Development Of Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the genetic reversion of attenuated vaccines or infection of immunocompromised hosts, as well as the likely tumorgenicity of deactivated viruses, are essential safety issues. In addition, all microorganisms cannot be used as live vaccines, since some of them are extremely virulent and others are intrinsically immune evasive [175,176].…”
Section: Development Of Vaccinesmentioning
confidence: 99%
“…Recently, nanoparticles have caught attention as a promising approach to the development of a new generation of vaccines, since the nanoparticles can both serve as a carrier for the antigen and behave as an adjuvant in many cases. In addition, nano-based vaccines can protect antigens against premature degradation and provide sustained release, enhanced antigen stability, and provide targeted delivery of an immunogen, as well as increase the period of antigen exposure and uptake by antigen presenting cells (APCs) [42,175]. Furthermore, nanoparticles are able to interact with immune machineries, inducing cellular and humoral immunological responses.…”
Section: Nano-based Vaccinesmentioning
confidence: 99%
“… 9 Novavax is currently developing COVID-19 vaccines using VLPs with full-length glycoproteins adjuvanted with Matrix M1. 118 , 123 , 130 Jung et al also used MERS-CoV spike protein NPs with alum to induce specific IgG antibodies in mice. 11 The spike protein NPs had a diameter of 35 nm, which increased to 80 nm when the NPs were formulated with alum.…”
Section: Nanoparticles As Immunogenic Agents For Vaccinesmentioning
confidence: 99%
“…For cell-specific targeted vaccination strategies, NPs with dimensions of ∌100 nm have been generally found to be good for cellular uptake by DCs via phagocytosis, since they resemble the natural targets for DCs, such as viruses or bacteria. 118 Several studies have found that the submicron size is optimal for mucosal cell uptake and that NPs less than 200 nm in size are more readily transported by draining lymph nodes. 140 NPs with sizes of 20–200 nm have long circulation times and become enriched in lymph nodes, leading to enhanced lymphatic transport, allowing direct access to lymphoid-node-resistant DCs.…”
Section: Nanoparticles As Immunogenic Agents For Vaccinesmentioning
confidence: 99%
“…In terms of SARS-CoV-2, mRNA-based nanovaccines have been developed using LNPs as carriers to protect mRNAs from degradation by extracellular RNases and to efficiently deliver mRNAs to immune cells and thereby trigger the translation of antigen proteins [ [115] , [116] , [117] , [118] ]. Moreover, the sustained release of mRNAs from LNPs leads to continuous protein translation, stimulating the production of high antibody titers and enhanced B cell and T cell immune responses [ 119 ].…”
Section: Nano-based Vaccinesmentioning
confidence: 99%